Consumer Value dan Behavioural Intention dalam TikTok Live Streaming: Menguji Peran Karakteristik Streamer - leonardo davidsi sipayung (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Along with current technological developments, live streaming is present as a popular activity and entertainment that is in great demand by online users. Previous researchers have examined the effect of streamer characteristics on consumer value perceptions in influencing consumer purchase intentions. Most of the previous research focused on consumer purchase intention. Departing from this research gap, this study aims to analyze the relationship between consumer perceived value and consumer behavioral intentions in TikTok live streaming through the role of streamer characteristics. The constructs used are streamer characteristics consisting of (beauty, humor, warmth, passion, and expertise), consumer value consisting of (hedonic value and utilitarian value), and behavioral intention consisting of (watching intention and gift-giving intention). The data analysis technique uses Structural Equation Modeling (SEM) with SmartPLS 4.0 software by testing 450 respondents who are live-streaming TikTok users. The results of the study show that beauty, humor, and warmth have a significant effect on encouraging consumer hedonic values, while passion and expertise have a significant effect on encouraging consumer utilitarian values. Then hedonic values and utilitarian values have a significant influence in encouraging watching intention and gift-giving intentions in live streaming. This research also provides theoretical and practical contributions, making it useful for streamers/sellers in increasing consumer behavioral intentions on TikTok live streaming.